Factors influencing sustainable employment of persons with acquired brain injury (ABI) or spinal cord injury (SCI): A qualitative study evaluating the perspective of health and work professionals - Finger, Monika E.; Karcz, Katarzyna; Schiffmann, Barbara; Staubli, Stefan; Hund-Georgiadis, Margret; Escorpizo, Reuben (Frontiers in Rehabilitation Sciences, 2023)
Background The number of persons with acquired brain injury (ABI) or spinal cord injury (SCI) who leave the labor market early despite successfully return to work post-injury, demonstrates the challenge for them to remain employed. Evidence on how enabling and hindering factors influence daily work across the lifespan and how they affect employment-related services is scarce. Professionals directly involved in work integration can add to this evidence through their experiential knowledge. Purpose To identify and explore the factors that enable or hinder sustainable employment for persons with ABI or SCI from the perspective of health and work professionals. Methods We conducted 23 semi-structured interviews with professionals in Switzerland, directly involved in work reintegration and retention of persons with ABI or SCI. Interviews were transcribed verbatim and thematically analyzed. Results Participants identified three main themes related to the concept of 'sustainable employment'. First, the value and impact of initial work integration; an early, multidisciplinary, person-centered work integration, with the early involvement of employers is ideal. A good match between the worker and the workplace is sought. Second, critical factors for long-term sustainable work: the main risks for persons with ABI are changing supervisors, workplace restructuring and the introduction of new technologies, while deteriorating health and the occurrence of secondary health problems are the greatest risk for persons with SCI. Third, the relevance of knowledge, experience and attitudes of professionals; Knowledge of the consequences of an ABI or SCI, the legal basis and the social security process, and the attitude of professionals towards the injured worker were considered important. Conclusions From the professional's perspective, enabling and hindering factors for sustainable employment in the long-term are fundamentally very similar for persons with ABI and SCI. But different physical, mental and neuropsychological effects call for individually adapted measures. While persons with SCI primarily require ongoing medical care, conscious management of changes in the workplace is critical for persons with ABI. For both groups, an easily accessible counseling and support service should be established for work-threatening problems in the long-term. Furthermore, diagnosis-specific training programs for professionals of employment-related services and disability management should be developed.